JOMO and FOMO in tourism as seen by university students - Wojcieszak-Zbierska, Monika (Turystyka i Rozwój Regionalny, 2023)
Today, the tourism industry offers a broad variety of innovative products andservices, and witnesses the emergence of FOMO and JOMO as an interesting phenomenon.These concepts provide strict guidelines for defining new products and services intended foruse by the tourists. Hence, this paper attempts to describe both of these behaviors in thecontext of tourism.It also focuses on presenting selected results of research carried out with a group of studentsof the Poznań University of Life Sciences. The study provides grounds for concluding that thestudents are inclined to spend their holidays in quiet offline places. While they find it attractiveto stay in a location with no Internet connection, they also believe that holidays with no accessto social media can take no longer than 1–2 days.